Dinosaur Adventures - Bromage, Fran (Essex, United Kingdom : Miles Kelly Publishing Ltd., 2018)
This fantastic collection of original dinosaur tales features lots of amazing characters for young readers to enjoy. Meet a T rex who think's he's the best, a shy and clumsy Ankylosaurus, a super-speedy Velociraptor and a Diplodocus with some totally crazy ideas!
5+
Keywords: Reading (Elementary); Dinosaur -- Fiction; Children's stories, English